Hardness analysis of remineralization primary teeth enamel after the application gel of duck eggshell extract (anas platyrhynchos domesticus) with consentration 20% and 40% in vitro - Agusmawanti, Prima; Niam, Mohammad Husnun; Sasanti, Galuh Eka (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background : Children are a population that has a high potential to be exposed to caries. Calcium deficiency due to demineralization of the enamel can cause a decrease in hardness during caries pathway. It can be anticipated with the application of re-mineralizing materials. Duck eggshells are contain high amount of calcium. This research aimed to examine the effect of duck eggshell extract gel (Anas plathyrhynchos domesticus) on the enamel hardness of primary teeth.Methods : This research is an experimental laboratory type using a pre and post-test control group design. There were 3 treatment groups with 4 samples in each group, which consisted of application of duck eggshell extract gel (Anas plathyrhynchos domesticus) with a concentration of 20% and 40%, and casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) paste. Sample application was carried out 42 times in 14-day intervals. Then the sample was measured with vickers microhardness tester. The data were processed by using Paired T-Test, Kruskal-Wallis, and Post Hoc Mann-Whitney statistical tests.Results : showed that there were significant differences in the samples before and after the application of duck eggshell extract gel (Anas plathyrhynchos domesticus) (p<0.05). Significant differences were also found in the three groups (p<0.05). The group that experienced the highest increase in hardness was the 20% duck eggshell extract gel (Anas plathyrhynchos domesticus) treatment group.Conclusion : was that duck eggshell extract gel (Anas plathyrhynchos domesticus) with a concentration of 20% was effective in increasing the hardness of primary tooth enamel